(untitled) (Journal of the College of Basic Education, 2022)
Social tendency is the presence of all desirable traits and the absence of social tendency is the presence of all undesirable traits, and accordingly, social tendency becomes a criterion for mental health, and the degree of social inclination shown by the individual becomes a measure of normal behavior. Hence there is a need to study social tendency among adolescents and the factors affecting this tendency. The importance of social tendency is clear as it is closely related to empathy, cooperation, altruistic behavior and positive attitudes towards others. The aim of the current research is to reveal the evolutionary path of social inclination among adolescents and its relationship to the variables of gender, age, and housing location (rural, city).The sample includes (120) male and female students. Social tendency scale which has been prepared by Grandle (1975) and has been translated to Arabic by Riyad Malkoush (1996), has been adopted in this study. The data was statistically processed and analyzed using the statistical methods (one-sample t-test, one-way analysis of variance, Scheffe post-test and multiple regression). The researchers conclude that adolescents have high level of social tendency developed according to age. The researchers set number of recommendations including: Parents should develop the adolescent’s tendency to understand others, help him, and encourage his desire to do so..